2021
DOI: 10.3390/s21144758
|View full text |Cite
|
Sign up to set email alerts
|

Graph-Based Deep Learning for Medical Diagnosis and Analysis: Past, Present and Future

Abstract: With the advances of data-driven machine learning research, a wide variety of prediction problems have been tackled. It has become critical to explore how machine learning and specifically deep learning methods can be exploited to analyse healthcare data. A major limitation of existing methods has been the focus on grid-like data; however, the structure of physiological recordings are often irregular and unordered, which makes it difficult to conceptualise them as a matrix. As such, graph neural networks have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 203 publications
0
60
1
Order By: Relevance
“…It then leverages the shadow dataset and the corresponding predictions to train the surrogate model for model extraction attack, which has been formulated in Eq. (5). Following this framework, recent works [162,198] have investigated the GNN model extraction attacks with different levels of knowledge on shadow dataset and training graph of the target model.…”
Section: Methods Of Privacy Attack On Gnnsmentioning
confidence: 99%
See 1 more Smart Citation
“…It then leverages the shadow dataset and the corresponding predictions to train the surrogate model for model extraction attack, which has been formulated in Eq. (5). Following this framework, recent works [162,198] have investigated the GNN model extraction attacks with different levels of knowledge on shadow dataset and training graph of the target model.…”
Section: Methods Of Privacy Attack On Gnnsmentioning
confidence: 99%
“…For example, GNNs have been used to process electronic health record (EHR) of patients for diagnosis prediction [109]. GNNs are also deployed to better capture the graph signal of brain activity for medical analysis [5]. To ensure the privacy of sensitive data of patients, privacy-preserving GNNs are required for the applications in healthcare domain.…”
Section: Applications Of Privacy Preserving Gnnsmentioning
confidence: 99%
“…In fact, artificial intelligence, specifically machine learning and deep learning, has contributed to tackling multiple challenges in the diagnosis of different diseases. Since their emergence, a wide range of research has been carried out with breakthrough results [2][3][4][5]. When symptoms are visible, images of the infected area are collected, and computer vision and image processing algorithms and techniques are applied to extract features that are fed to the diagnostic models.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they check both areas simultaneously for further assurance. Moreover, previous studies in this domain have not applied deep learning and transfer learning models, despite their success in the diagnosis of different diseases [2][3][4][5]. In this work, we seek to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world graphs, such as medical and economic networks, are associated with sensitive information about individuals and their activities and cannot always be made public. Releasing pre-trained models provides an opportunity for using the private knowledge beyond company boundaries [2]. However, recent works have shown that GNNs are vulnerable to membership inference attacks [9,18].…”
mentioning
confidence: 99%